Protective Effect of Propolis against Aluminium Chloride Reproductive Toxicity Histopathological and Ultrastruchtural Study (Global Journal of Medical Research, 2020)
Human impact on the environment was steadily increasing the amounts of aluminum in the ecosystems. This element accumulated in plants and water. Potentially increased its harmful effect; particularly, it induced free radical-mediated cytotoxicity and reproductive toxicity. Propolis was a resinous material collected by bees from bud and exudates of the plants, mixed with bee enzymes, pollen, and wax. Due to its waxy nature and mechanical properties, bees used propolis in the construction and repair of their hives, and as a protective barrier against external invaders, or weathering threats, Current antimicrobial properties of propolis, was helping for wound healing, treatment of burns, herpes simplex and genital herpes. The present work studied the protective effect of propolis against the reproductive toxicity of aluminum chloride in male rats.
Keywords: male albino rat Aluminum chloride toxicity Propolis